EVALUATING THE IMPLEMENTATION OF THE MERDEKA BELAJAR–KAMPUS MERDEKA (MBKM) PROGRAM TO SUPPORT HIGHER EDUCATION KEY PERFORMANCE INDICATORS: A CIPP AND IPOO EVALUATION IN A JOURNALISM STUDY PROGRAM - Yuliati Yuliati; Dita Haryani; Yosi Oktavia (Journal Neosantara Hybrid Learning, 2025)
This study evaluates the implementation of the Merdeka Belajar Kampus Merdeka (MBKM) program and its contribution to the achievement of Key Performance Indicators (IKU) in the S1 Journalism Study Program, Faculty of Social and Political Sciences, University of Bengkulu. MBKM serves as Indonesia’s national higher education reform, providing students with flexible learning opportunities outside the campus through experiential and industry-linked activities. Guided by principles of educational evaluation, this study employs the Context–Input–Process–Product (CIPP) model and the Input–Process–Output–Outcome (IPOO) framework to systematically assess program relevance, resource readiness, implementation quality, outputs, and institutional outcomes. Using a descriptive qualitative approach, data were collected through interviews, questionnaires, observations, documentation, and literature review. Informants were selected using purposive sampling, including program managers, lecturers, students, and external partners. Data were analyzed through reduction, display, conclusion drawing, and triangulation. The findings indicate that MBKM implementation significantly contributes to the achievement of IKU particularly IKU-2 (student learning experience outside campus) and IKU-6 (partnership with external institutions). Two strategic mechanisms were identified as the most influential: (1) diversification and collaboration with industry and community partners, and (2) integration of MBKM activities with faculty research through research assistance schemes. MBKM also generated tangible outputs such as student publications, intellectual property, documentary works, and enhanced professional competencies. This study provides empirical evidence on how program evaluation frameworks can be effectively applied to assess MBKM performance and offers strategic recommendations for strengthening experiential learning in journalism education.